Immune checkpoint Inhibitor related myocarditis reported through the FDA adverse event reporting system: pharmacovigilance trends in reporting and outcomes - Reeves, David J.; Leffers, Kevin; Rao, Vijay U. (Frontiers in Oncology, 2025)
IntroductionAs the use of immune checkpoint inhibitors (ICIs) continues to expand, it is important to be mindful of rare but serious side effects such as myocarditis. Multiple analyses of adverse effect databases have demonstrated an association between ICIs and myocarditis; however, given the rapid implementation of therapeutic use, introduction of multiple new ICIs, and expanding indications, it is unclear if trends are evolving in reporting and outcomes.MethodsWe analyzed the FDA Adverse Event Reporting System to investigate the association between ICIs and myocarditis and trends in myocarditis outcomes among reports submitted between 2012 and the first quarter of 2023.ResultsAfter removal of duplicate cases, 1,326 myocarditis cases were reported to the database in patients receiving ICIs. Of these, the majority of reported cases were in males (62%) and the median age was 69 years. Consistent with the increase in utilization, the number of cases reported per year increased with each passing year. The reporting odds ratio (ROR) for all ICI drugs included in the analysis was 30.1 (95% confidence interval: 28.4-32.0). RORs for the individual drugs ranged from 12.3 for durvalumab to 168.5 for nivolumab/ relatlimab. The overall fatality rate of all cases was 37%. A significant difference in fatality rate among reported cases was present when comparing outcomes in 2018 and 2022 (45% vs 33%, respectively, p=0.017).DiscussionMyocarditis continues to be associated with immune checkpoint inhibitors, with the number of reported cases increasing consistent with increasing utilization; however, the outcomes may be improving with less cases being reported as fatal.